Freud against God - Toegel, Christfried, author.
1 online resource (98 pages)
Keywords: Freud Against God traces the development of Freud's atheism, from his youth through to Moses and Monotheism, published in 1939.Christfried Toegel takes a largely chronological approach, tracing how biographical developments in Freud's life and political events gradually led to his conviction that it is "a greater risk if we maintain our present attitude to religion than if we give it up." The book considers Freud's life, his writing, and the influence of politics and society. Chapter 1 covers the genesis of Freud's critical attitude towards religion and the influence of Ludwig Brne, Charles Darwin, and John Stuart Mill. Chapter 2 focuses on Freud's critiques of religion in his writing between 1907 and 1939. Chapter 3 describes how Freud dealt with the deaths of his daughter and his grandson, and with cancer and death. Chapter 4 focuses on religion, politics, and society, particularly the role of the Catholic Church in relation to Freud and psychoanalysis.Written by a leading Freud scholar, this book provides a compact overview of Freud's atheism. Freud Against God will be of great interest to academics and scholars of Freud and religion.